Elastic Attention: Enhanced, then Sharpened Response to Auditory Input as Attentional Load Increases - Neelon, Michael F.; Williams, Justin C.; Garell, P. C. (Frontiers in Human Neuroscience, 2011)
A long debate in selective attention research is whether attention generally enhances sensory response or sharpens neural tuning by suppressing response to non-optimal input. A combination of the two processes may arise as a function of processing load: an uncertain listener might use a broad attentional filter to enhance responses to inputs generally (i.e., vigilance), yet employ sharpened tuning to increase focus on hard to discriminate targets. The present work used the greater signal gain, anatomical precision, and laterality separation of intracranial electrophysiological recordings (ECoG) to investigate these competing effects. Data were recorded from the perisylvian region of a single hemisphere in 5 epilepsy surgery patients performing a dichotic listening task in which they alternately attended toward, away from, or completely ignored (silent reading) tones presented to designated ears at varying presentation rates. Comparisons between the grand-averaged event-related potential (ERP) waveforms show a striking change in the effect of selective auditory attention across hemisphere with attentional load. At slower presentation rates (low load), ERPs were generally enhanced in a single hemisphere in response to either input channel and regardless of attended ear. This included a significant enhancement of ipsilateral input. This result is likely due to exogenous orientation to both ears and supports a broadly enhancing model of attention during conditions of low perceptual load. At the fastest rate, however, all responses to ipsilateral inputs in attention conditions were equivalent to ipsilateral ignore ERPs, while only response to attended inputs contralateral to grid location remained enhanced. This result supports an increasing suppression, or “sharpening”, of neural responses with increasing attentional load. These data provide support for an elastic model of attention in which attentional scope narrows with increasing load.